Preparation method of building material based on multi-source solid waste and high-strength insulation board
Patent Information
- Application Number
- CN202511959452.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-24
AI Technical Summary
其中,工业固废如油页岩渣(年排放量超5000万吨,富含SiO2、Al2O3但利用率不足30%)、氨碱白泥(纯碱工业副产物,含48~63%CaO但高碱性易导致土壤碱化,堆存利用率不足20%)、硅锰渣、铅锌渣、钒钛矿渣(冶金工业副产物,累计堆存量超10亿吨,硅钙铝成分未被有效利用)、废光伏板(退役量年均增长20%,玻璃基材含60~83%SiO2但金属杂质与有机胶膜分离难度大,回收利用率不足 15%)、氟石膏、锂渣(化工副产物,含SO42-与活性硅铝成分但易吸潮结块);生活及包装固废如餐厨贝壳废弃物(年产生量超1000万吨,含高纯度CaCO3却多被填埋)、快递木包装(年消耗量超2000万立方米,多作为垃圾焚烧或填埋,未实现碳资源回收)、废加气混凝土(建筑拆改副产物,含40~60%iO2与20~30% CaO但再生利用仅停留在低附加值填料阶段),此类多源固废累计堆存已占用超1000万亩土地,不仅造成资源浪费,更易引发土壤污染、地下水污染等环境问题
本发明在以钙质材料(氨碱白泥、餐厨贝壳废弃物)、硅质材料(油页岩渣、废光伏板、硅锰渣)、铁铝质材料(铅锌渣、钒钛矿渣、粉煤灰、煤矸石)为原料制备高温煅烧产物的过程中,通过调控多个工艺发挥协同作用,形成最佳匹配,使得煅烧产物形成特定的晶相结构,实现其优异的早中后期性能,可以替代硅酸盐水泥熟料使用。
Smart Images

Figure CN122079555B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of solid waste recycling, and more specifically, to a method for preparing building materials based on multi-source solid waste and a high-strength insulation board. Background Technology
[0002] With the rapid development of industrial scale and the acceleration of urbanization, the output of industrial solid waste and domestic / packaging solid waste (hereinafter collectively referred to as "multi-source solid waste") in my country has been increasing year by year. Among them, industrial solid waste includes oil shale slag (annual discharge of over 50 million tons, rich in SiO2 and Al2O3 but with a utilization rate of less than 30%), ammonia-alkali white mud (a by-product of the soda ash industry, containing 48-63% CaO, but its high alkalinity easily leads to soil alkalization, and its stockpiling utilization rate is less than 20%), ferrosilicon manganese slag, lead-zinc slag, vanadium-titanium ore slag (a by-product of the metallurgical industry, with a cumulative stockpile of over 1 billion tons, and its silicon, calcium, and aluminum components not being effectively utilized), waste photovoltaic panels (with an average annual growth of 20% in decommissioning, the glass substrate containing 60-83% SiO2, but the separation of metal impurities from organic films is difficult, and the recycling rate is less than 15%), fluorogypsum, and lithium slag (a chemical by-product, containing SO4). 2- It contains active silicon and aluminum components but is prone to moisture absorption and clumping; domestic and packaging solid waste such as kitchen shell waste (annual production exceeds 10 million tons, containing high purity CaCO3 but mostly landfilled), express delivery wooden packaging (annual consumption exceeds 20 million cubic meters, mostly incinerated or landfilled, without carbon resource recovery), and waste aerated concrete (a byproduct of building demolition, containing 40-60% IO2 and 20-30% CaO, but recycling is only at the low value-added filler stage). The cumulative accumulation of such multi-source solid waste has occupied more than 10 million mu of land, which not only causes resource waste but also easily leads to environmental problems such as soil pollution and groundwater pollution.
[0003] Although existing technologies attempt to apply single solid wastes to building materials (such as replacing part of cement with fly ash and crushing waste aerated concrete into coarse aggregate), the following limitations still exist: the current solid waste resource utilization and building materials fields face technical bottlenecks such as "difficulty in synergistic use of multi-source solid wastes, low activity of low-carbon powders, conflict in thermal insulation mechanical properties, and lack of utilization of natural fibers," making it difficult to meet the comprehensive needs of "high-value utilization of solid waste," "low-carbon building," and "high-performance thermal insulation." Summary of the Invention
[0004] To address the aforementioned technical problems in related technologies, this invention provides a method for preparing building materials based on multi-source solid waste and a high-strength insulation board, which can solve the above problems.
[0005] To achieve the above-mentioned technical objectives, the technical solution of the present invention is implemented as follows: A method for preparing building materials based on multi-source solid waste includes the following steps: S1. Pretreatment of oil shale slag: First, the oil shale slag is screened using a vibrating screen to remove organic matter and other impurities. Then, it is crushed into oil shale slag particles with a particle size of 2-5mm in a jaw crusher. The oil shale slag particles are then dried in a 105℃ electric heating forced-air drying oven until they reach a constant weight for later use. Some of the dried oil shale slag particles are then ground in a cement ball mill to achieve a specific surface area of 200-300 m². 2 / kg of oil shale slag powder is available for use; S2. Pretreatment of ammonia-alkali white mud and kitchen shell waste: (1) Dry the ammonia-alkali white mud in a 105℃ electric heating blast drying oven to constant weight; (2) Wash the kitchen shell waste with high-pressure water and then air dry it in a cool place; put the air-dried kitchen shell waste into a jaw crusher to crush it into shell particles with a particle size of 2~5mm, and then put the shell particles into a 105℃ electric heating blast drying oven to constant weight; put the dried shell particles into a cement ball mill to grind them to a specific surface area of 200~300 m². 2 / kg of shell powder is prepared for use; (3) the dried ammonia-alkali white mud and shell powder are mixed evenly in a mass ratio of 2~4:1~3 to obtain mixture A; then the mixed mixture A is put into a cement mortar mixer and stirred for 60~90s, then water accounting for 8~10% of the mass of mixture A is added and stirred for 90~120s; after mixing evenly, it is put into a mold and pressed into a material cake one by a hydraulic press (the material cake thickness is 1~3cm and the diameter is 5~8cm), and the material cake one is placed in an electric heating blast drying oven to dry for 20~30min (drying) (4) After drying, the material cake is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 200℃, the heating rate is 4℃ / min, and then the temperature is held for 20~30min; then from 200℃ to the required temperature of 750℃~850℃, the heating rate is 5℃ / min, and then the temperature is held for 30~50min). After calcination, the material cake is cooled quickly by wind power, and then the cooled material cake is put into a cement ball mill and ground to a specific surface area of 400~500m². 2 / kg, yielding powder one; S3. Pre-treatment of waste photovoltaic panels: First, remove the attached materials (aluminum frame and rubber strip, etc.) from the waste photovoltaic panels. Then, use high-pressure water to remove the impurities and dust adsorbed on the surface of the photovoltaic panels. After natural drying, use a hammer crusher to crush the waste photovoltaic panels into pieces with a particle size ≤25mm. Then, put the blocky waste photovoltaic panels into a jaw crusher to crush them into waste photovoltaic panel particles with a particle size ≤2mm for later use. S4. Pretreatment of ferromanganese slag: First, the ferromanganese slag is screened using a hydrocyclone to maintain its slurry concentration at 25-40%, resulting in ferromanganese slag particles with particle sizes ≤0.109mm, 0.109-0.212mm, 0.212-0.380mm, and ≥0.380mm. Then, the four types of ferromanganese slag particles are placed in a 105℃ electric heating blast drying oven and dried to constant weight for later use. (3) The dried ferromanganese slag particles with particle sizes ≤0.109mm and ≥0.380mm are placed in a cement ball mill and ground to a specific surface area of 200-300m². 2 / kg of ferromanganese slag powder is available for use; S5, Pretreatment of lead-zinc slag and vanadium-titanium slag: (1) First, use a vibrating screen to separate lead-zinc slag and vanadium-titanium slag into particles with a particle size ≤2mm and particles with a particle size >2mm respectively; (2) Then, put the particles >2mm into a jaw crusher to crush them into particles with a particle size ≤2mm, and then mix them with the particles with a particle size ≤2mm obtained by screening and dry them in a 105℃ electric heating blast drying oven to constant weight to obtain lead-zinc slag particles and vanadium-titanium slag particles with a particle size ≤2mm; (3) Put the lead-zinc slag particles, vanadium-titanium slag particles and silicon manganese slag powder in S4 into a planetary ball mill at a mass ratio of 1~3:1:2~4 and mix them to obtain a particle mixture B with a particle size ≤2mm; S6. Pretreatment of fly ash / coal gangue: (1) Place fly ash in a 105℃ electric heating blast drying oven and dry it to constant weight. After drying, the fly ash is dispersed into fly ash particles with a particle size of ≤2mm by a planetary ball mill for later use; (2) Screen the coal gangue to separate particles of ≤2mm, particles of >2mm and organic impurities. Then put the particles of >2mm into a jaw crusher and crush them to ≤2mm particles. Then mix them with the ≤2mm particles obtained by screening and place them in a 105℃ electric heating blast drying oven to dry to constant weight; (3) Put fly ash particles with a particle size of ≤2mm and coal gangue particles with a particle size of ≤2mm into a planetary ball mill at a mass ratio of 2~4:1~3 and mix them to obtain a particle mixture C with a particle size of ≤2mm. S7. Pre-treatment of wooden packaging for express delivery: First, disassemble the wooden packaging, then saw it to a length <15cm and a cross-sectional area <30cm². 2 The waste wood packaging box fragments are then placed on a material rack, and the entire material rack is placed into a carbonization kettle. High-temperature flue gas is used to carbonize the waste wood packaging box fragments in the carbonization kettle (the temperature of the high-temperature flue gas is 500~700℃, and the carbonization time is 4~6h). The carbonized and cooled wood fragments are taken out of the carbonization kettle and placed in a jaw crusher to be crushed into carbon particles with a particle size ≤2mm for later use. Preparation of S8, Powder Cake II: Oil shale slag particles from S1, powder I from S2, waste photovoltaic panel particles from S3, granular mixture B from S5, and granular mixture C from S6 are mixed in a mass ratio of 10-15%:60-77%:5-10%:5-10%:3-5% to obtain mixture D. Carbon particles from S7 are added to mixture D, and the mixture is ball-milled to obtain a specific surface area of 300-400 m². 2 The mixture consists of a 1 kg / kg composite powder, in which carbon particles account for 5-8% of the total mass of the mixture D. The composite powder is then placed in a cement mortar mixer and mixed for 60-90 seconds. Water, accounting for 8-10% of the mass of the composite powder, is added and mixed for another 90-120 seconds. After uniform mixing, the mixture is placed in a mold and pressed into a cake (cake 2, 1-3 cm thick and 5-8 cm in diameter) using a hydraulic press. The cake 2 is then placed in an electric heating drying oven and dried for 20-30 minutes (drying temperature 100℃). S9. Preparation of Low-Carbon Powder II: Powder II is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 300℃ at a heating rate of 3℃ / min, then held for 25-35 min; then from 300℃ to 1100-1300℃ at a heating rate of 10℃ / min, then held for 25-35 min). After calcination, it is rapidly cooled by air to obtain the high-temperature calcined product. This product is then crushed into composite material particles I with a particle size ≤2mm using a jaw crusher. Composite material particles I are then ground in a cement ball mill to a specific surface area of 450-550 m². 2 / kg, yielding low-carbon powder II; Preparation of S10 and Powder 3: First, use a vibrating screen to remove impurities from fluorogypsum and lithium slag, then dry them in a 105℃ electric heating blast drying oven until constant weight. Then, put the dried fluorogypsum and lithium slag into a planetary ball mill at a mass ratio of 1~3:1 and mix them evenly to obtain Powder 3 for later use. S11. Pretreatment of Waste Aerated Concrete: First, the waste aerated concrete is screened using a vibrating screen to remove impurities such as bricks and organic matter. Then, large pieces of waste aerated concrete are sawn into blocks less than 25cm in length, less than 6cm in thickness, and less than 12cm in width using a woodworking saw. Next, the blocks are crushed into 1-3mm particles using a jaw crusher. The particles are then dried in a 105℃ electric heating forced-air drying oven until constant weight is achieved. A portion of the dried waste aerated concrete particles is then ground in a cement ball mill to achieve a specific surface area of 300-400 m². 2 / kg of waste aerated concrete powder is reserved for use; Preparation of S12 and Powder 4: Powder 1 from S2, oil shale slag powder from S1, ferrosilicon manganese slag powder from S4, fly ash particles from S6, powder 3 from S10, and silica fume are mixed evenly in a mass ratio of 13~18%:6~10%:24~28%:21~26%:7~11%:12~29% to obtain mixture E. A water-reducing agent is added to mixture E, and then it is ground in an ultrafine grinding mill to obtain a specific surface area of 1600~1800 m². 2 / kg of powder material four, of which the water-reducing agent accounts for 3~5% of the total mass of mixture E; S13. Preparation of coconut shell fiber: ① First, rinse the coconut shells with high-pressure water, then place them in a cool place to dry. Next, use a woodworking saw to cut the coconut shells into 6-8 cm long pieces. ② Immerse the cut pieces in a container containing deionized water and triacylglycerol hydrolase (the amount of triacylglycerol hydrolase is 0.4-0.6% of the mass of deionized water) for 3-5 hours, maintaining the solution temperature at 46-48℃. Then filter and remove the coconut shell pieces. ③ Place the pieces in a 0.3-0.7% sodium hydroxide solution and heat and pressurize them (temperature 8...). 5~100℃, pressure 10~13MPa), steam for 2.5~4h, and rinse the coconut shell fragments with clean water after steaming; ④ The rinsed coconut shell fragments are placed in a 70℃ electric hot air drying oven to dry to constant weight, and then put into a spinning machine to break them down into coarse fibers, and then rinsed with clean water; ⑤ The rinsed coarse fibers are placed in a 70℃ electric hot air drying oven to dry to constant weight, and then loosened using a carding machine to obtain coconut shell fibers with a diameter of 12~24μm, and then the coconut shell fibers with a diameter of 12~24μm are made into two sizes of 19mm and 5~25mm in length for later use; S14. Preparation of Ultra-High Performance Concrete (UHPC): A dry mixture of powder and coarse / fine aggregates (component 1) is placed in a cement mortar mixer and dry-mixed for 210-250 seconds. The powder includes powder 2 and powder 4, and the coarse / fine aggregates are coarse and fine sand. The mass percentages of coarse / fine sand, powder 2, and powder 4 are 45-58%:32-40%:10-15%. Water is divided into three equal parts by mass and mixed separately with defoamer, retarder, and high-performance expanding agent. After complete dissolution, two parts of the solution are poured onto the dry mixture (component 1) and stirred for 180-210 seconds until the dry mixture becomes a dough-like consistency. Then, the remaining 1 part... Add the solution and stir for 180-210 seconds to bring the slurry to a viscous state. The amounts of expanding agent, defoamer, retarder, and water are 1.5-2.9‰, 0.77-0.96‰, 0.38-0.58‰, and 18-20% of the total mass of the powder, respectively. Slowly add the fiber to the mixer while it is stirring over 340-390 seconds. After the fiber is added, stir for another 210-250 seconds to obtain ultra-high performance concrete. The fiber includes steel fiber and 19mm long coconut shell fiber from S13. The amount of coconut shell fiber and steel fiber added accounts for 0.1-0.4 vol.% and 1.7-2.3 vol.% of the total volume of ultra-high performance concrete, respectively. (The ultra-high performance concrete is poured into a mold and compacted with a vibrating table. After standard curing for 1 day, the mold is removed. Immediately after demolding, it is placed in a steam curing chamber at a temperature of 80-90℃ for 3 days to obtain UHPC fireproof board.)
[0006] S15. Preparation of foamed concrete: The dry materials and 5-25mm long coconut shell fibers from S13 are placed in a cement mortar mixer and mixed evenly according to the specified ratio. The dry materials are powder II from S9, waste aerated concrete powder from S11, and powder IV from S12. The mass percentages of powder II, waste aerated concrete powder, and powder IV are 35-60%:5-10%:35-55%. The amount of coconut shell fiber added is 0.1-0.3 vol.% of the total volume of the foamed concrete. Then, 48-55% of the water is added according to a water-to-material ratio of 52-72%. Mix 6-10‰ of a foam stabilizer with warm water at ℃ for 80-100 seconds, then add 0.55-0.70‰ of aluminum powder (by weight of dry materials) and mix for 30-50 seconds to obtain foamed concrete. (Ensure the pouring temperature of the foamed concrete is 45-50℃. After pouring into the mold, allow it to stand for 8-10 hours under steam curing at 55-65℃, then perform standard curing for 2 days before demolding. Immediately after demolding, place it in a steam curing chamber at 80-90℃ for 3 days to obtain foamed concrete slabs.)
[0007] Optionally, the main mineral composition of the oil shale slag in S1 is quartz, and its main chemical components and contents are: CaO 0.5~3%, SiO2 55~70%, Al2O3 10~25%, Fe2O3 5~12%, MgO 0.5~2%, K2O 0.1~3%, Na2O 0.01~1.5%, and the loss on ignition of the oil shale slag is 3~10%.
[0008] Optionally, the main mineral composition of the ammonia-alkali white mud in S2 is: calcium carbonate, calcium sulfate, calcium chloride, etc., and its main chemical components and contents are: CaO 48~63%, SiO2 1~7%, Al2O3 1~5%, Fe2O3 0.1~3%, MgO 1~6%, and the loss on ignition of the ammonia-alkali white mud is 3~22%.
[0009] Optionally, the main chemical components and contents of the waste photovoltaic panels in S3 are: SiO2 60~83%, CaCl2 0.1~5%, NaCl 16~38%, and the loss on ignition of the waste photovoltaic panels is 0.1~8%.
[0010] Optionally, the main mineral composition of the ferromanganese slag in S4 is: quartz, straight manganese pyroxene, fir olivine, etc., and its main chemical composition and content are: CaO 16~23%, SiO2 35~47%, Al2O3 15~25%, Fe2O3 0.1~3%, MgO 2~8%, K2O 0.1~2%, MnO 4~15%, and the loss on ignition of the ferromanganese slag is 1~4%.
[0011] Optionally, the main mineral composition of the vanadium-titanium slag in S5 is magnesia rhodochrosite and perovskite, with the following main chemical components and contents: SiO2 27~33%, CaO 30~35%, Al2O3 8~15%, MgO 8~12%, Fe2O3 5~10%, SO3 0.1~3%, K2O+Na2O 0.1~2%, TiO2 5~10%, and the loss on ignition of the vanadium-titanium slag is 0.1~3%.
[0012] Optionally, the main mineral composition of fly ash in S6 is quartz and mullite, with the following main chemical components and contents: SiO2 40~50%, Al2O3 25~35%, CaO 5~12%, Fe2O3 5~8%, MgO 0.1~2%, SO3 2~10%, K2O 0.5~2%, Na2O 0.1~0.5%, and the loss on ignition of fly ash is 3~7%; the main mineral phases of coal gangue are quartz and clay minerals (kaolinite, illite, montmorillonite and muscovite), siderite, etc., with the following main chemical components and contents: SiO2 40~60%, Al2O3 20~30%, K2O 1~5%, MgO 1~3%, Na2O+K2O 1~4%, Fe2O3 5~15%, CaO 1~5%, and the loss on ignition of coal gangue is 25~40%.
[0013] Optionally, the main chemical element composition and content of the express delivery wooden packaging in S7 are: C 32~58%, H 1~5%, O 25~48%, N 0.01~1%, S 0.01~2%, moisture content of the express delivery wooden packaging is 2~6%, ash content is 1~6%, fixed carbon is 5~11%, and volatile matter is 65~80%.
[0014] Optionally, the main mineral composition of fluorinated gypsum in S10 is CaSO4·2H2O and CaSO4·1 / 2H2O, and its main chemical composition and content are: SO3 30~50%, CaO 20~40%, SiO2 2~5%, P2O5 1~3%, MgO 0.01~2%, Na2O 0.01~1%, Fe2O3 0.01~5%, K2O 0.01~1%, and the loss on ignition of fluorinated gypsum is 15~25%; the main mineral composition of lithium slag is quartz, spodumene, gypsum, etc., and its chemical composition and content are: CaO 22~30%, SiO2 45~55%, Al2O3 16~22%, SO3 18~23%, Fe2O3 0.1~3%.
[0015] Optionally, the main mineral composition of the waste aerated concrete in S11 is quartz, tobermorite, calcite and CSH gel, and its main chemical composition and content are: SiO2 40~60%, Al2O3 3~8%, CaO 20~30%, MgO 1~5%, Fe2O3 1~5%, SO3 1~5%, K2O+Na2O 0.1~2%, and the loss on ignition of the waste aerated concrete is 5~15%.
[0016] Optionally, the main mineral component of the silica fume in S12 is quartz, with a particle size of 0.1~1µm. Its SiO2 content, apparent density, specific surface area, and pozzolanic activity index are 91.38%, 2.18 g / m³, and 2.18 g / m³, respectively. 3 19400m 2 / kg, 110%; the water-reducing agent is a high-performance polycarboxylate powder water-reducing agent with a water reduction rate of >30%; the maximum feed particle size of the ultrafine grinding mill is ≤20mm, and the finished particle size is 325~2500 mesh.
[0017] Optionally, the main chemical elements of the coconut shell fiber in S13 are: C 45~55%, H 3~8%, O 40~52%, N 0.2~1.5%, S 0.01~0.2%, and the coconut shell fiber contains 40~50% total cellulose, 15~20% lignin and 30~40% α-cellulose.
[0018] Optionally, the composition of coarse and fine sand in S14 is coarse sand and fine sand, with a mass percentage of coarse sand to fine sand of 1~3:1; the particle size of coarse sand is 0.212~0.380mm, and the particle size of fine sand is 0.109~0.212mm; the mass percentage of ferromanganese slag particles with a particle size of 0.109~0.212mm and quartz sand in the fine sand is 1~2:1, and the mass percentage of ferromanganese slag particles with a particle size of 0.212~0.380mm and quartz sand in the coarse sand is 1~3:1; the defoamer is at least one of tributyl phosphate or organosilicon defoamer, the retarder is boric acid, and the main chemical composition and content of the high-performance expanding agent are SiO2 5~10%, Al2O3 25~30%, Fe2O3 1~7%, CaO 30~40%, MgO 1~3%, SO3 18~23%, and the loss on ignition of the high-performance expanding agent is 0.1~1%; the fibers used in UHPC are steel fibers and coconut shell fibers. The steel fibers used are two types: 0.2mm in diameter and 13mm in length, and 0.16mm in diameter and 6mm in length. The two types of steel fibers (i.e., the two types with diameters of 0.2mm and 0.16mm) are used in a mass percentage ratio of 1~2:1; the cement mortar mixer is used at a low speed during the preparation of UHPC slurry.
[0019] Optionally, the foam stabilizer in S15 is prepared from trinitrotoluene, distilled water and sodium stearoyl lactylate in a ratio of 6~9%: 80~92%: 2~11%; the active Al content of the aluminum powder is ≥93%.
[0020] Optionally, the jaw crushers in S1, S2, S3, S5, S6, S7, S9 and S11 have a feed particle size ≤250mm and an output particle size ≤10mm.
[0021] Optionally, the rotational speed of the cement ball mill in S1, S2, S4, S8, S9 and S11 is 48 r / min.
[0022] Optionally, in S2 and S8, the compression molding pressure is 15~25 MPa.
[0023] Optionally, the pellets obtained by pressing in S2 and S8 are more easily calcined in a muffle furnace to obtain high-quality raw materials.
[0024] Optionally, in S2, S8, S15 and S16, the rotation speed of the cement mortar mixer during low-speed mixing is: 140±5 r / min rotation and 62±5 r / min revolution, or 285±10 r / min rotation and 125±10 r / min revolution.
[0025] Optionally, the feed size of the hammer crusher in S3 is ≤450mm, and the discharge size is ≤25mm.
[0026] Optionally, the dispersion time of the planetary ball mill in S5, S6 and S10 is 15~20min, and the rotation speed is 200r / min.
[0027] Optionally, the cooling in S9 includes: first cooling to 1000°C at a wind speed of 18~20°C / min, and then cooling to room temperature. The purpose is to improve the quality of the low-carbon powder by controlling the cooling temperature; specifically, by cooling (from 1000°C to room temperature at a rate of not less than 100°C / min to obtain low-carbon powder with excellent performance in the early, middle and late stages), the formation of C2S in the powder is controlled.
[0028] A high-strength thermal insulation board includes a polyurethane board in the middle layer, and foamed concrete board layers and ultra-high performance concrete board layers are arranged sequentially on both sides of the polyurethane board. A steel grid is provided between the foamed concrete board layers and the ultra-high performance concrete board layers. The foamed concrete board layers are formed by pouring prepared foamed concrete, and the ultra-high performance concrete board layers are formed by pouring prepared ultra-high performance concrete.
[0029] The beneficial effects of this invention are: In the process of preparing high-temperature calcined products using calcareous materials (ammonia-alkali mud, kitchen waste shells), siliceous materials (oil shale slag, waste photovoltaic panels, ferromanganese slag), and ferroaluminous materials (lead-zinc slag, vanadium-titanium ore slag, fly ash, coal gangue) as raw materials, this invention achieves optimal matching by regulating multiple processes to enable the calcined products to form specific crystal phase structures, thereby realizing their excellent early, middle, and late-stage performance and making them a substitute for silicate cement clinker.
[0030] This invention, through specific crystalline phase structure design and performance control, applies low-carbon powder made from high-temperature calcination products to the production of UHPC composite fireproof and heat-insulating boards, enabling UHPC boards and foamed concrete boards to have higher physical and mechanical properties, significantly superior to existing ordinary silicate cement clinker; at the same time, the low-carbon powder described in this invention also has excellent characteristics of significantly low alkali, rapid setting, rapid hardening, high strength, low carbon, and low chloride ion content.
[0031] The low-carbon powder prepared by this invention has a significant carbon reduction effect. It incorporates carbonaceous materials made from express delivery wooden packaging and waste photovoltaic panels during the firing process, which can reduce the firing temperature by more than 100°C compared with silicate cement clinker and reduce energy consumption by more than 10%. At the same time, the calcined product uses all solid waste raw materials in the firing process and does not use limestone, reducing CO2 emissions by more than 20%, which can significantly reduce the production cost of enterprises.
[0032] The waste materials used in this invention include: oil shale slag, ammonia-alkali white mud, waste photovoltaic panels, ferromanganese slag, lead-zinc slag, vanadium-titanium ore slag, fly ash, coal gangue, express delivery wooden packaging, silica fume, fluorogypsum, lithium slag, coconut shell, and waste aerated concrete. The heat transfer coefficient of the high-strength insulation board prepared is ≤0.26 W / m². 2 .K replaces traditional insulating materials such as rock wool and extruded polystyrene board for industrial and civil building walls, which is in line with the current development concept of ultra-low energy consumption in green public buildings. In addition, the invention improves the utilization rate of industrial solid waste and uses solid waste to replace a large amount of quartz sand and silica fume in the traditional UHPC production, which significantly reduces the production cost of enterprises.
[0033] This invention utilizes waste aerated concrete as lightweight aggregate to reduce the density of foamed concrete. At the same time, the addition of polyurethane boards in the system design can reduce the thermal conductivity of high-strength insulation boards, ensuring good thermal insulation performance and effect, and achieving a balance between density, strength and thermal insulation performance.
[0034] The ultrafine powder used in the preparation of UHPC in this invention involves grinding powders of different particle sizes together. The coarse particles serve as the grinding medium, leveraging the synergistic effect of particle size distribution to achieve better dispersion of the ultrafine silica fume raw material, reducing agglomeration. When used in the finished product, it can better promote the pozzolanic effect and micro-aggregate effect, and also prevent alkali-aggregate reaction.
[0035] The high-strength insulation board of this invention has fire resistance and flame retardancy, small deformation coefficient, light density, strong seismic performance, good durability, low production cost, and excellent low-elasticity shock absorption performance. Its mechanical performance indicators (strength), physical performance indicators (density, thermal conductivity), and combustion performance meet the requirements of the indicators in "Cement-based Foam Insulation Board" (JC / T 2200-2013) and "Classification of Combustion Performance of Building Materials and Products" (GB8624-2012). Attached Figure Description
[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0037] The present invention will now be described in further detail with reference to the accompanying drawings.
[0038] Figure 1 This is a structural diagram of the high-strength insulation board described in an embodiment of the present invention; Figure 2 This is a flow chart illustrating the manufacturing process of the high-strength insulation board described in the embodiments of the present invention; Figure 3 This is a process flow diagram of the UHPC board fabrication process described in the embodiments of the present invention; Figure 4 This is the preparation process flow of the foamed concrete board described in the embodiments of the present invention; Figure 5 This is the XRD pattern of the hardened foamed concrete described in the embodiments of the present invention; Figure 6 These are SEM images of the pore structure of the hardened foamed concrete body described in the embodiments of the present invention, taken at different magnifications. Figure 7 This is a SEM image of the cross-section of the hardened foamed concrete body described in the embodiment of the present invention; Figure 8 yes Figure 7 A magnified view of region 1 in the middle; Figure 9 yes Figure 7 A magnified view of region 2 in the middle; Figure 10 yes Figure 7 A magnified view of region 3 in the middle; Figure 11 yes Figure 8 Enlarged view of areas 1-3 in the middle; Figure 12 yes Figure 8 A magnified view of region 4 in the middle; Figure 13 yes Figure 12 Enlarged view of region 4-2 in the middle; Figure 14 yes Figure 9 The central area 5 uses magnified images at different magnifications. Detailed Implementation
[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0040] like Figures 1-2The diagram shows the structure and manufacturing process of the high-strength insulation board of this application. The high-strength insulation board is a 200mm thick composite board with three layers: outer, inner, and outer. The outer layer of the composite board is a 20mm thick UHPC, and the middle 160mm layer is a 90mm thick polyurethane board + double-sided foamed concrete (35mm thick on each side). Two layers of ø8 steel reinforcement mesh (composed of horizontal and vertical reinforcement) are designed on the two sides of the middle layer close to the UHPC. The mesh size is (170~230)mm × (170~230)mm, and the nodes are tied with flame-bonded wire. In order to fix the steel reinforcement mesh, tie rods with a height of 190~198mm are set in the UHPC boards on both sides. The tie rods are designed as "I" shapes and are made of ø14 steel bars welded together. The number of tie rods is set according to the number of nodes in each row of steel reinforcement mesh. The tie rods are 50mm away from the edge of the board and are evenly distributed according to the number. In the prefabrication of high-strength thermal insulation boards, the construction is carried out according to the following steps: ① First, erect the formwork for a 20mm thick UHPC board on one side and install tie bolts. After the concrete is poured, vibrated, demolded, and cured; ② Use the single-sided molded UHPC board as the bottom formwork, lay and tie the reinforcing bars, erect the formwork, and then pour the foamed concrete on one side; ③ After the foamed concrete on one side has initially set, install the polyurethane board. The polyurethane board has clips that fit tightly against the initially set foamed concrete. After installation, erect the formwork again, and then pour the foamed concrete on the other side, followed by curing to the specified age; ④ Use the molded UHPC and foamed concrete as the bottom formwork to complete the formwork erection, pouring, demolding, and curing of the outermost UHPC board. Figures 3-4 The diagram shows the preparation process of the UHPC board and the foamed concrete board of this application. The following is a detailed description through specific embodiments. Example 1:
[0041] The preparation of UHPC boards and foamed concrete boards includes the following steps: S1. Pretreatment of oil shale slag: First, the oil shale slag is screened using a vibrating screen to remove organic matter and other impurities. Then, it is crushed into oil shale slag particles with a particle size of 2-5mm in a jaw crusher. The oil shale slag particles are then dried in a 105℃ electric heating forced-air drying oven until they reach a constant weight for later use. Some of the dried oil shale slag particles are then ground in a cement ball mill to achieve a specific surface area of 200 m². 2 / kg of oil shale slag powder is available for use; S2. Pretreatment of ammonia-alkali white mud and kitchen shell waste: (1) Dry the ammonia-alkali white mud in a 105℃ electric heating blast drying oven until constant weight; (2) Wash the kitchen shell waste with high-pressure water and then air dry it in a cool place; put the air-dried kitchen shell waste into a jaw crusher to crush it into shell particles with a particle size of 2~5mm, and then put the shell particles into a 105℃ electric heating blast drying oven to dry until constant weight; put the dried shell particles into a cement ball mill to grind them to a specific surface area of 200m². 2 / kg of shell powder is prepared for use; (3) the dried ammonia-alkali white mud and shell powder are mixed evenly at a mass ratio of 2:1 to obtain mixture A; then the mixed mixture A is put into a cement mortar mixer and stirred for 60s, then water accounting for 8% of the mass of mixture A is added and stirred for 90s; after mixing evenly, it is put into a mold and pressed into a material cake one by a hydraulic press (the material cake is 1cm thick and 5cm in diameter). The material cake one is placed in an electric heating blast drying oven and dried for 20min (drying temperature) (4) After drying, the material cake is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 200℃, the heating rate is 4℃ / min, and then hold for 20min; then from 200℃ to the required temperature of 750℃, the heating rate is 5℃ / min, and then hold for 30min). After calcination, the material cake is quickly cooled by wind, and then the cooled material cake is put into a cement ball mill and ground to a specific surface area of 400m². 2 / kg, yielding powder one; S3. Pre-treatment of waste photovoltaic panels: First, remove the attached materials (aluminum frame and rubber strip, etc.) from the waste photovoltaic panels. Then, use high-pressure water to remove the impurities and dust adsorbed on the surface of the photovoltaic panels. After natural drying, use a hammer crusher to crush the waste photovoltaic panels into pieces with a particle size ≤25mm. Then, put the blocky waste photovoltaic panels into a jaw crusher to crush them into waste photovoltaic panel particles with a particle size ≤2mm for later use. S4. Pretreatment of ferromanganese slag: First, the ferromanganese slag is screened by hydrocyclone to maintain its slurry concentration at 25% to obtain ferromanganese slag particles with particle sizes ≤0.109mm, 0.109~0.212mm, 0.212~0.380mm and ≥0.380mm; then, the four types of ferromanganese slag particles are placed in a 105℃ electric heating blast drying oven and dried to constant weight for later use; (3) The dried ferromanganese slag particles with particle sizes ≤0.109mm and ≥0.380mm are placed in a cement ball mill and ground to a specific surface area of 200m². 2 / kg of ferromanganese slag powder is available for use; S5, Pretreatment of lead-zinc slag and vanadium-titanium slag: (1) First, use a vibrating screen to separate lead-zinc slag and vanadium-titanium slag into particles with a particle size ≤2mm and particles with a particle size >2mm respectively; (2) Then, put the particles >2mm into a jaw crusher to crush them into particles with a particle size ≤2mm, and then mix them with the particles with a particle size ≤2mm obtained by screening and dry them in a 105℃ electric heating blast drying oven to constant weight to obtain lead-zinc slag particles and vanadium-titanium slag particles with a particle size ≤2mm; (3) Put the lead-zinc slag particles, vanadium-titanium slag particles and silicon manganese slag powder in S4 into a planetary ball mill at a mass ratio of 1:1:2 and mix them to obtain a particle mixture B with a particle size ≤2mm; S6. Pretreatment of fly ash / coal gangue: (1) Place fly ash in a 105℃ electric heating blast drying oven and dry it to constant weight. After drying, the fly ash is dispersed into fly ash particles with a particle size of ≤2mm by a planetary ball mill for later use; (2) Screen the coal gangue to separate particles of ≤2mm, particles of >2mm and organic impurities. Then put the particles of >2mm into a jaw crusher and crush them to ≤2mm particles. Then mix them with the ≤2mm particles obtained by screening and place them in a 105℃ electric heating blast drying oven to dry to constant weight; (3) Put fly ash particles with a particle size of ≤2mm and coal gangue particles with a particle size of ≤2mm into a planetary ball mill at a mass ratio of 2:1 and mix them to obtain a particle mixture C with a particle size of ≤2mm. S7. Pre-treatment of wooden packaging for express delivery: First, disassemble the wooden packaging, then saw it to a length <15cm and a cross-sectional area <30cm². 2 The wood fragments are then placed on a material rack, and the entire material rack is placed into a carbonization kettle. The waste wood packaging box fragments in the carbonization kettle are carbonized using high-temperature flue gas (the temperature of the high-temperature flue gas is 500℃, and the carbonization time is 4h). The carbonized and cooled wood fragments are taken out of the carbonization kettle and placed in a jaw crusher to be crushed into carbon particles ≤2mm for later use. Preparation of S8, Powder Cake II: Oil shale slag particles from S1, powder I from S2, waste photovoltaic panel particles from S3, granular mixture B from S5, and granular mixture C from S6 are mixed in a mass ratio of 10%:77%:5%:5%:3% to obtain mixture D. Carbon particles from S7 are added to mixture D, and the mixture is ball-milled to obtain a specific surface area of 300 m². 2 The first batch of powder is mixed at a mass of / kg, in which the carbon particles account for 5% of the total mass of the mixture D. Then, the first batch of powder is put into a cement mortar mixer and mixed for 60s. Then, water accounting for 8% of the mass of the first batch of powder is added and mixed for 90s. After the mixture is evenly mixed, the mixture is put into a mold and pressed into a second batch of material cakes (the second batch of material cakes is 1cm thick and 5cm in diameter) by a hydraulic press. The second batch of material cakes is placed in an electric heating blast drying oven and dried for 20min (drying temperature is 100℃). S9. Preparation of Low-Carbon Powder II: Powder II is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 300℃ at a heating rate of 3℃ / min, then held for 25 min; then from 300℃ to 1100℃ at a heating rate of 10℃ / min, then held for 25 min). After calcination, it is rapidly cooled by air to obtain the high-temperature calcined product. This product is then crushed by a jaw crusher to a combined material particle size ≤2mm. The combined material particle size is then ground in a cement ball mill to a specific surface area of 450m². 2 / kg, yielding low-carbon powder II; Preparation of S10 and Powder 3: First, use a vibrating screen to remove impurities from fluorogypsum and lithium slag, then dry them in a 105℃ electric heating blast drying oven until constant weight. Then, put the dried fluorogypsum and lithium slag into a planetary ball mill at a mass ratio of 1:1 and mix them evenly to obtain Powder 3 for later use. S11. Pretreatment of Waste Aerated Concrete: First, the waste aerated concrete is screened using a vibrating screen to remove impurities such as bricks and organic matter. Then, large pieces of waste aerated concrete are sawn into blocks less than 25cm in length, less than 6cm in thickness, and less than 12cm in width using a woodworking saw. Next, the blocks are crushed into 1-3mm particles using a jaw crusher. The particles are then dried in a 105℃ electric heating forced-air drying oven until constant weight is achieved. A portion of the dried waste aerated concrete particles is then ground in a cement ball mill to achieve a specific surface area of 300m². 2 / kg of waste aerated concrete powder is reserved for use; Preparation of S12 and Powder 4: Powder 1 from S2, oil shale slag powder from S1, ferromanganese slag powder from S4, fly ash particles from S6, powder 3 from S10, and silica fume are mixed evenly in a mass ratio of 13%:6%:24%:21%:7%:29% to obtain mixture E. A water-reducing agent is added to mixture E, and then it is ground in an ultrafine grinding mill to obtain a specific surface area of 1600 m². 2 / kg of powder material four, of which the water-reducing agent accounts for 3% of the total mass of mixture E; S13. Preparation of coconut shell fiber: ① First, wash the coconut shells with high-pressure water, then place them in a cool place to dry. Next, use a woodworking saw to cut the coconut shells into 6cm long pieces; ② Immerse the cut pieces in a container containing deionized water and triacylglycerol hydrolase (the amount of triacylglycerol hydrolase is 0.4% of the mass of deionized water) for 3 hours, maintaining the solution temperature at 46℃. Then filter and remove the coconut shell pieces; ③ Place the pieces in a 0.3% sodium hydroxide solution and heat and pressurize them (temperature 85℃). ④ After steaming for 2.5 hours under 10 MPa pressure, the coconut shell fragments are rinsed with clean water. ⑤ The rinsed coconut shell fragments are dried in a 70℃ electric hot air drying oven until constant weight, and then put into a spinning machine to break them down into coarse fibers, and then rinsed with clean water. ⑥ The rinsed coarse fibers are dried in a 70℃ electric hot air drying oven until constant weight, and then loosened using a carding machine to obtain coconut shell fibers with a diameter of 12~24μm. The coconut shell fibers with a diameter of 12~24μm are then made into two sizes with a length of 19mm and 5~25mm for later use. S14. Preparation of Ultra-High Performance Concrete (UHPC): A dry mixture of powder and coarse / fine aggregates (component 1) is placed in a cement mortar mixer and dry-mixed for 210 seconds. The powder includes powder 2 and powder 4, and the coarse / fine aggregates are coarse and fine sand, with a mass percentage of 58%:32%:10% for coarse / fine sand, powder 2, and powder 4. Water is divided into three equal parts by mass and mixed thoroughly with defoamer, retarder, and high-performance expanding agent, respectively. After complete dissolution, two parts of the solution are poured onto the dry mixture and stirred for 180 seconds until the dry mixture becomes a dough-like consistency. Then, the remaining one part of the solution is added and stirred for another 180 seconds until the slurry reaches a viscous flow state. The expanding agent, defoamer, and... The dosages of retarder and water are 1.5‰, 0.77‰, 0.38‰, and 18% of the total mass of powder, respectively. The fiber is slowly added to the mixer in a stirring state within 340s. After the fiber is added, the mixer is stirred for another 210s to obtain ultra-high performance concrete. The fiber includes steel fiber and 19mm long coconut shell fiber from S13. The amount of coconut shell fiber and steel fiber added accounts for 0.1 vol.% and 1.7 vol.% of the total volume of ultra-high performance concrete, respectively. (UHPC fireproof board can be obtained by pouring ultra-high performance concrete into a mold and compacting it with a vibrating table. After standard curing for 1 day, the mold is removed. After demolding, it is immediately placed in a steam curing chamber at a temperature of 80℃ for 3 days.)
[0042] S15. Preparation of foamed concrete: The dry materials and 5-25mm long coconut shell fibers from S13 are placed in a cement mortar mixer and mixed evenly in proportion. The dry materials are powder II from S9, waste aerated concrete powder from S11, and powder IV from S12. The mass percentages of powder II, waste aerated concrete powder, and powder IV are 60%:5%:35%. The amount of coconut shell fiber added is 0.1 vol.% of the total volume of foamed concrete. Then, 48℃ warm water and 6‰ of the total water volume of foam stabilizer are added at a water-material ratio of 52%. The mixture is stirred for 80 seconds. Then, 0.55‰ of the total mass of aluminum powder is added and stirred for 30 seconds to obtain foamed concrete. (Ensure that the pouring temperature of the foamed concrete is 45℃. After pouring into the mold, it is statically steamed at 55℃ for 8 hours, and then standard cured for 2 days before demolding. Immediately after demolding, it is placed in a steam curing chamber at 80℃ for 3 days to obtain foamed concrete boards.)
[0043] The mass ratio of coarse sand to fine sand in the coarse sand is 1:1. The mass ratio of ferrosilicon manganese slag particles (0.109~0.212mm) to fine quartz sand in the fine sand is 1:1. The mass ratio of ferrosilicon manganese slag particles (0.212~0.380mm) to coarse quartz sand in the coarse sand is 1:1. Two types of steel fibers (0.2mm and 0.16mm in diameter) are used in a 1:1 mass ratio. The proportions of trinitrotoluene, distilled water, and sodium stearoyl lactylate in the foam stabilizer are 6%:92%:2%. In S2 and S8, the pressing pressure is 15 MPa. In S5, S6, and S10, the planetary ball mill dispersion time is 15 min. In S9, cooling includes: first cooling to 1000℃ at a wind speed of 18℃ / min, then cooling to room temperature.
[0044] The powder prepared according to S10, a 1:1 mixture of fluorogypsum and lithium slag, meets the technical specifications specified in GB / T 21371-2019 "Industrial By-product Gypsum Used in Cement". The mixed industrial by-product gypsum contains 86% CaSO4·2H2O and a total of 86% CaSO4 (specification requirement ≥75%), 0.42% chloride ion content (specification requirement ≤0.5%), a pH value of 4.7 (specification requirement ≤5), and radioactive material limits that meet the requirements of GB 6566 (internal exposure index ≤1.0, external exposure index ≤1.0).
[0045] In Example 1, the physicochemical properties of powder one in S2 are shown in Table 1, the chemical composition analysis and activity index of low carbon powder two in S9 are shown in Tables 2 and 3, the radioactivity results of powder four in S12 are shown in Table 4, the performance indicators of UHPC board in S14 are shown in Table 5, and the performance indicators of foamed concrete board in S15 are shown in Table 6.
[0046] Table 1. Physicochemical properties of powder 1 in Examples 1-S2 ; *Note: refers to the technical specifications of JC / T 621-2021, "Quicklime for Silicate Building Products".
[0047] Table 2 Chemical composition of low-carbon powder II in Example 1-S9 ; Table 3 Activity index of low-carbon powder II in Example 1 – S9
[0048] ; Note: * indicates the test method in GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)".
[0049] Table 4. Radioactivity test results of dry materials in Examples 1-S12 ; *Note: These are the test requirements in GB 6566-2010, "Limits of Radionuclides in Building Materials".
[0050] Table 5 Performance indicators of UHPC boards in Examples 1-S14 ; Note: * represents T / CECS 10107-2020, Technical Requirements for Ultra-High Performance Concrete (UHPC); ** represents GB / T 31387-2025, Ultra-High Performance Concrete; *** represents GB 8624-2012, Classification of Combustion Performance of Building Materials and Products.
[0051] Table 6 Performance indicators of foamed concrete boards in Examples 1-S15 ; Note: * indicates the test index requirements in "Foamed Concrete" JG / T 266-2011.
[0052] Example 2 The preparation of UHPC boards and foamed concrete boards includes the following steps: S1. Pretreatment of oil shale slag: First, the oil shale slag is screened using a vibrating screen to remove organic matter and other impurities. Then, it is crushed into oil shale slag particles with a particle size of 2-5mm in a jaw crusher. The oil shale slag particles are then dried in a 105℃ electric heating forced-air drying oven until they reach a constant weight for later use. Some of the dried oil shale slag particles are then ground in a cement ball mill to achieve a specific surface area of 250 m². 2 / kg of oil shale slag powder is available for use; S2. Pretreatment of ammonia-alkali white mud and kitchen shell waste: (1) Dry the ammonia-alkali white mud in a 105℃ electric heating blast drying oven until constant weight; (2) Wash the kitchen shell waste with high-pressure water and then air dry it in a cool place; put the air-dried kitchen shell waste into a jaw crusher to crush it into shell particles with a particle size of 2~5mm, and then put the shell particles into a 105℃ electric heating blast drying oven to dry until constant weight; put the dried shell particles into a cement ball mill to grind them to a specific surface area of 250 m². 2 / kg of shell powder is prepared for use; (3) The dried ammonia-alkali white mud and shell powder are mixed evenly at a mass ratio of 3:2 to obtain mixture A; then the mixed mixture A is put into a cement mortar mixer and stirred for 80s, then water accounting for 9% of the mass of mixture A is added and stirred for 110s; after mixing evenly, it is put into a mold and pressed into a material cake one by a hydraulic press (the material cake is 2cm thick and 6cm in diameter), and the material cake one is placed in an electric heating blast drying oven to dry for 25min (drying temperature (4) After drying, the material cake is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 200℃, the heating rate is 4℃ / min, and then the temperature is held for 25min; then from 200℃ to the required temperature of 800℃, the heating rate is 5℃ / min, and then the temperature is held for 40min). After calcination, the material cake is cooled quickly by wind power, and then the cooled material cake is placed in a cement ball mill and ground to a specific surface area of 450m². 2 / kg, yielding powder one; S3. Pre-treatment of waste photovoltaic panels: First, remove the attached materials (aluminum frame and rubber strip, etc.) from the waste photovoltaic panels. Then, use high-pressure water to remove the impurities and dust adsorbed on the surface of the photovoltaic panels. After natural drying, use a hammer crusher to crush the waste photovoltaic panels into pieces with a particle size ≤25mm. Then, put the blocky waste photovoltaic panels into a jaw crusher to crush them into waste photovoltaic panel particles with a particle size ≤2mm for later use. S4. Pretreatment of ferromanganese slag: First, the ferromanganese slag is screened by hydrocyclone to maintain its slurry concentration at 30% to obtain ferromanganese slag particles with particle sizes ≤0.109mm, 0.109~0.212mm, 0.212~0.380mm and ≥0.380mm; then, the four types of ferromanganese slag particles are placed in a 105℃ electric heating blast drying oven and dried to constant weight for later use; (3) The dried ferromanganese slag particles with particle sizes ≤0.109mm and ≥0.380mm are placed in a cement ball mill and ground to a specific surface area of 250m². 2 / kg of ferromanganese slag powder is available for use; S5, Pretreatment of lead-zinc slag and vanadium-titanium slag: (1) First, use a vibrating screen to separate lead-zinc slag and vanadium-titanium slag into particles with a particle size ≤2mm and particles with a particle size >2mm respectively; (2) Then, put the particles >2mm into a jaw crusher to crush them into particles with a particle size ≤2mm, and then mix them with the particles with a particle size ≤2mm obtained by screening and dry them in a 105℃ electric heating blast drying oven to constant weight to obtain lead-zinc slag particles and vanadium-titanium slag particles with a particle size ≤2mm; (3) Put the lead-zinc slag particles, vanadium-titanium slag particles and silicon manganese slag powder in S4 into a planetary ball mill at a mass ratio of 2:1:3 and mix them to obtain a particle mixture B with a particle size ≤2mm; S6. Pretreatment of fly ash / coal gangue: (1) Place fly ash in a 105℃ electric heating blast drying oven and dry it to constant weight. After drying, the fly ash is dispersed into fly ash particles with a particle size of ≤2mm by a planetary ball mill for later use; (2) Screen the coal gangue to separate particles of ≤2mm, particles of >2mm and organic impurities. Then put the particles of >2mm into a jaw crusher and crush them to ≤2mm particles. Then mix them with the ≤2mm particles obtained by screening and place them in a 105℃ electric heating blast drying oven to dry to constant weight; (3) Put fly ash particles with a particle size of ≤2mm and coal gangue particles with a particle size of ≤2mm into a planetary ball mill at a mass ratio of 3:2 and mix them to obtain a particle mixture C with a particle size of ≤2mm. S7. Pre-treatment of wooden packaging for express delivery: First, disassemble the wooden packaging, then saw it to a length <15cm and a cross-sectional area <30cm². 2 The wood fragments are then placed on a material rack, and the entire material rack is placed into a carbonization kettle. The waste wood packaging box fragments in the carbonization kettle are carbonized using high-temperature flue gas (the temperature of the high-temperature flue gas is 600℃, and the carbonization time is 5h). The carbonized and cooled wood fragments are taken out of the carbonization kettle and placed in a jaw crusher to be crushed into carbon particles ≤2mm for later use. Preparation of S8, Powder Cake II: Oil shale slag particles from S1, powder I from S2, waste photovoltaic panel particles from S3, granular mixture B from S5, and granular mixture C from S6 are mixed in a mass ratio of 12%:70%:7%:7%:4% to obtain mixture D. Carbon particles from S7 are added to mixture D, and the mixture is ball-milled to obtain a specific surface area of 350 m². 2 The first batch of powder is mixed at a mass of / kg, in which the carbon particles account for 7% of the total mass of the mixture D. Then, the first batch of powder is put into a cement mortar mixer and mixed for 75s. Then, water accounting for 9% of the mass of the first batch of powder is added and mixed for 110s. After the mixture is evenly mixed, the mixture is put into a mold and pressed into a second batch of material cakes (the second batch of material cakes is 2cm thick and 6cm in diameter) by a hydraulic press. The second batch of material cakes is placed in an electric heating blast drying oven and dried for 25min (drying temperature is 100℃). S9. Preparation of Low-Carbon Powder II: Powder II is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 300℃ at a heating rate of 3℃ / min, then held for 30min; then from 300℃ to 1200℃ at a heating rate of 10℃ / min, then held for 30min). After calcination, it is rapidly cooled by air to obtain the high-temperature calcined product. This product is then crushed into composite material particles I with a particle size ≤2mm using a jaw crusher. Composite material particles I are then ground in a cement ball mill to a specific surface area of 500m². 2 / kg, yielding low-carbon powder II; Preparation of S10 and Powder 3: First, use a vibrating screen to remove impurities from fluorogypsum and lithium slag, then dry them in a 105℃ electric heating blast drying oven until constant weight. Then, put the dried fluorogypsum and lithium slag into a planetary ball mill at a mass ratio of 2:1 and mix them evenly to obtain Powder 3 for later use. S11. Pretreatment of Waste Aerated Concrete: First, the waste aerated concrete is screened using a vibrating screen to remove impurities such as bricks and organic matter. Then, large pieces of waste aerated concrete are sawn into blocks less than 25cm in length, less than 6cm in thickness, and less than 12cm in width using a woodworking saw. Next, the blocks are crushed into 1-3mm particles using a jaw crusher. The particles are then dried in a 105℃ electric heating forced-air drying oven until constant weight is achieved. A portion of the dried waste aerated concrete particles is then ground in a cement ball mill to achieve a specific surface area of 350 m². 2 / kg of waste aerated concrete powder is reserved for use; Preparation of S12 and Powder 4: Powder 1 from S2, oil shale slag powder from S1, ferrosilicon manganese slag powder from S4, fly ash particles from S6, powder 3 from S10, and silica fume are mixed evenly in a mass ratio of 16%:8%:26%:23%:9%:18% to obtain mixture E. A water-reducing agent is added to mixture E, and then it is ground in an ultrafine grinding mill to obtain a specific surface area of 1700 m². 2 / kg of powder material four, of which the water-reducing agent accounts for 4% of the total mass of mixture E; S13. Preparation of coconut shell fiber: ① First, rinse the coconut shells with high-pressure water, then place them in a cool place to dry. Next, use a woodworking saw to cut the coconut shells into 7cm long pieces. ② Immerse the cut pieces in a container containing deionized water and triacylglycerol hydrolase (the amount of triacylglycerol hydrolase is 0.5% of the mass of deionized water) for 4 hours, maintaining the solution temperature at 47℃. Then filter and remove the coconut shell pieces. ③ Place the pieces in a 0.5% sodium hydroxide solution and heat and pressurize them (temperature 95℃). ④ After steaming for 3 hours at 12 MPa pressure, the coconut shell fragments were rinsed with clean water. ⑤ The rinsed coconut shell fragments were dried in a 70℃ electric hot air drying oven to constant weight, and then put into a spinning machine to break them down into coarse fibers, and then rinsed with clean water. ⑥ The rinsed coarse fibers were dried in a 70℃ electric hot air drying oven to constant weight, and then loosened using a carding machine to obtain coconut shell fibers with a diameter of 12~24μm. The coconut shell fibers with a diameter of 12~24μm were then made into two sizes with a length of 19mm and 5~25mm for later use. S14. Preparation of Ultra-High Performance Concrete (UHPC): A dry mixture of powder and coarse / fine aggregates (component 1) is placed in a cement mortar mixer and dry-mixed for 230 seconds. The powder includes powder 2 and powder 4, and the coarse / fine aggregates are coarse and fine sand, with a mass percentage of 52%:36%:12% for coarse / fine sand, powder 2, and powder 4. Water is divided into three equal parts by mass and mixed separately with defoamer, retarder, and high-performance expanding agent. After complete dissolution, two parts of the solution are poured onto the dry mixture and stirred for 200 seconds until the dry mixture becomes a dough-like consistency. Then, the remaining one part of the solution is added and stirred for another 200 seconds until the slurry reaches a viscous flow state. The expanding agent, defoamer, and... The dosages of retarder and water are 2.3‰, 0.90‰, 0.50‰, and 19% of the total mass of powder, respectively. The fiber is slowly added to the mixer in a stirring state over 360 seconds. After the fiber is added, the mixer is stirred for another 230 seconds to obtain ultra-high performance concrete. The fiber includes steel fiber and 19mm long coconut shell fiber from S13. The amount of coconut shell fiber and steel fiber added accounts for 0.3 vol.% and 2.0 vol.% of the total volume of ultra-high performance concrete, respectively. (UHPC fireproof board can be obtained by pouring ultra-high performance concrete into a mold, compacting it with a vibrating table, demolding it after 1 day of standard curing, and immediately placing it in a steam curing chamber at 85℃ for 3 days after demolding.)
[0053] S15. Preparation of foamed concrete: The dry materials and 5-25mm long coconut shell fibers from S13 are placed in a cement mortar mixer and mixed evenly in proportion. The dry materials are powder II from S9, waste aerated concrete powder from S11, and powder IV from S12. The mass percentages of powder II, waste aerated concrete powder, and powder IV are 48%:7%:45%. The amount of coconut shell fiber added is 0.2 vol.% of the total volume of foamed concrete. Then, 52℃ warm water and 8‰ of the total water volume of foam stabilizer are added at a water-material ratio of 60%. The mixture is stirred for 90 seconds. Then, 0.65‰ of the total mass of aluminum powder of the dry materials is added and stirred for 42 seconds to obtain foamed concrete. (Ensure that the pouring temperature of the foamed concrete is 48℃. After pouring into the mold, it is statically steamed at 60℃ for 9 hours, and then standard cured for 2 days before demolding. Immediately after demolding, it is placed in a steam curing chamber at 85℃ for 3 days to obtain foamed concrete boards.)
[0054] The mass percentage of coarse sand to fine sand in the coarse sand is 2:1. The mass percentage of fine sand containing ferrosilicon manganese slag particles (0.109~0.212mm) and fine quartz sand is 1.5:1. The mass percentage of coarse sand containing ferrosilicon manganese slag particles (0.212~0.380mm) and coarse quartz sand is 2:1. Two types of steel fibers (0.2mm and 0.16mm in diameter) are used in a mass percentage ratio of 1.5:1. The foam stabilizer contains trinitrotoluene, distilled water, and sodium stearoyl lactylate in a ratio of 8%:86%:6%. In S2 and S8, the pressing pressure is 20 MPa. In S5, S6, and S10, the planetary ball mill dispersion time is 17 min. In S9, cooling includes first cooling to 1000℃ at a wind speed of 19℃ / min, and then cooling to room temperature.
[0055] The powder prepared by S10, a 2:1 mixture of fluorogypsum and lithium slag, meets the technical specifications specified in GB / T 21371-2019 "Industrial By-product Gypsum Used in Cement". The mixed industrial by-product gypsum contains 89% CaSO4·2H2O and 89% total CaSO4, with a chloride ion content of 0.38%, a pH value of 4.4, and radioactive material limits that meet the requirements of GB 6566.
[0056] In Example 2, the physicochemical properties of powder one in S2 are shown in Table 7, the chemical composition analysis and activity index of low carbon powder two in S9 are shown in Tables 8 and 9, the radioactivity results of powder four in S12 are shown in Table 10, the performance indicators of UHPC board in S14 are shown in Table 11, and the performance indicators of foamed concrete board in S15 are shown in Table 12.
[0057] Table 7 Physicochemical properties of powder 1 in Example 2-S2 ; *Note: refers to the technical specifications of JC / T 621-2021, "Quicklime for Silicate Building Products".
[0058] Table 8 Chemical composition of low-carbon powder II in Example 2-S9 ; Table 9 Activity index of low-carbon powder II in Examples 2–S9
[0059] ; Note: * indicates the test method in GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)".
[0060] Table 10. Radioactivity test results of the dry material in Example 2-S12 ; *Note: These are the test requirements in GB 6566-2010, "Limits of Radionuclides in Building Materials".
[0061] Table 11 Performance indicators of UHPC boards in Example 2-S14 ; Note: * represents T / CECS 10107-2020, Technical Requirements for Ultra-High Performance Concrete (UHPC); ** represents GB / T 31387-2025, Ultra-High Performance Concrete; *** represents GB 8624-2012, Classification of Combustion Performance of Building Materials and Products.
[0062] Table 12 Performance indicators of foamed concrete boards in Example 2-S15 ; Note: * indicates the test index requirements in "Foamed Concrete" JG / T 266-2011.
[0063] Example 3 The preparation of UHPC boards and foamed concrete boards includes the following steps: S1. Pretreatment of oil shale slag: First, the oil shale slag is screened using a vibrating screen to remove organic matter and other impurities. Then, it is crushed into oil shale slag particles with a particle size of 2-5mm in a jaw crusher. The oil shale slag particles are then dried in a 105℃ electric heating forced-air drying oven until they reach a constant weight for later use. Some of the dried oil shale slag particles are then ground in a cement ball mill to achieve a specific surface area of 300 m². 2 / kg of oil shale slag powder is available for use; S2. Pretreatment of ammonia-alkali white mud and kitchen shell waste: (1) Dry the ammonia-alkali white mud in a 105℃ electric heating blast drying oven until constant weight; (2) Wash the kitchen shell waste with high-pressure water and then air dry it in a cool place; put the air-dried kitchen shell waste into a jaw crusher to crush it into shell particles with a particle size of 2~5mm, and then put the shell particles into a 105℃ electric heating blast drying oven to dry until constant weight; put the dried shell particles into a cement ball mill to grind them to a specific surface area of 300 m². 2 / kg of shell powder for later use; (3) The dried ammonia-alkali white mud and shell powder are mixed evenly in a mass ratio of 4:3 to obtain mixture A; then the mixed mixture A is put into a cement mortar mixer and stirred for 90s, then water accounting for 10% of the mass of mixture A is added and stirred for 120s; after mixing evenly, it is put into a mold and pressed into a material cake one by a hydraulic press (the material cake is 3cm thick and 8cm in diameter), and the material cake one is placed in an electric heating blast drying oven to dry for 30min (drying (4) After drying, the material cake is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 200℃, heating rate is 4℃ / min, and then hold for 30min; then from 200℃ to the required temperature of 850℃, heating rate is 5℃ / min, and then hold for 50min). After calcination, the material cake is quickly cooled by wind power, and then the cooled material cake is placed in a cement ball mill and ground to a specific surface area of 500m². 2 / kg, yielding powder one; S3. Pre-treatment of waste photovoltaic panels: First, remove the attached materials (aluminum frame and rubber strip, etc.) from the waste photovoltaic panels. Then, use high-pressure water to remove the impurities and dust adsorbed on the surface of the photovoltaic panels. After natural drying, use a hammer crusher to crush the waste photovoltaic panels into pieces with a particle size ≤25mm. Then, put the blocky waste photovoltaic panels into a jaw crusher to crush them into waste photovoltaic panel particles with a particle size ≤2mm for later use. S4. Pretreatment of ferromanganese slag: First, the ferromanganese slag is screened by hydrocyclone to maintain its slurry concentration at 40% to obtain ferromanganese slag particles with particle sizes ≤0.109mm, 0.109~0.212mm, 0.212~0.380mm and ≥0.380mm; then, the four types of ferromanganese slag particles are placed in a 105℃ electric heating blast drying oven and dried to constant weight for later use; (3) The dried ferromanganese slag particles with particle sizes ≤0.109mm and ≥0.380mm are placed in a cement ball mill and ground to a specific surface area of 300m². 2 / kg of ferromanganese slag powder is available for use; S5, Pretreatment of lead-zinc slag and vanadium-titanium slag: (1) First, use a vibrating screen to separate lead-zinc slag and vanadium-titanium slag into particles with a particle size ≤2mm and particles with a particle size >2mm respectively; (2) Then, put the particles >2mm into a jaw crusher to crush them into particles with a particle size ≤2mm, and then mix them with the particles with a particle size ≤2mm obtained by screening and dry them in a 105℃ electric heating blast drying oven to constant weight to obtain lead-zinc slag particles and vanadium-titanium slag particles with a particle size ≤2mm; (3) Put the lead-zinc slag particles, vanadium-titanium slag particles and silicon manganese slag powder in S4 into a planetary ball mill at a mass ratio of 3:1:4 and mix them to obtain a particle mixture B with a particle size ≤2mm; S6. Pretreatment of fly ash / coal gangue: (1) Place fly ash in a 105℃ electric heating blast drying oven and dry it to constant weight. After drying, the fly ash is dispersed into fly ash particles with a particle size of ≤2mm by a planetary ball mill for later use; (2) Screen the coal gangue to separate particles of ≤2mm, particles of >2mm and organic impurities. Then put the particles of >2mm into a jaw crusher and crush them to ≤2mm particles. Then mix them with the ≤2mm particles obtained by screening and place them in a 105℃ electric heating blast drying oven to dry to constant weight; (3) Put fly ash particles with a particle size of ≤2mm and coal gangue particles with a particle size of ≤2mm into a planetary ball mill at a mass ratio of 4:3 and mix them to obtain a particle mixture C with a particle size of ≤2mm. S7. Pre-treatment of wooden packaging for express delivery: First, disassemble the wooden packaging, then saw it to a length <15cm and a cross-sectional area <30cm². 2 The wood fragments are then placed on a material rack, and the entire material rack is placed into a carbonization kettle. The waste wood packaging box fragments in the carbonization kettle are carbonized using high-temperature flue gas (the temperature of the high-temperature flue gas is 700℃, and the carbonization time is 6h). The carbonized and cooled wood fragments are taken out of the carbonization kettle and placed in a jaw crusher to be crushed into carbon particles ≤2mm for later use. Preparation of S8, Powder Cake II: Oil shale slag particles from S1, powder I from S2, waste photovoltaic panel particles from S3, granular mixture B from S5, and granular mixture C from S6 are mixed in a mass ratio of 15%:60%:10%:10%:5% to obtain mixture D. Carbon particles from S7 are added to mixture D, and the mixture is ball-milled to obtain a specific surface area of 400 m². 2 The first batch of powder is mixed at a mass of / kg, in which the carbon particles account for 8% of the total mass of the mixture D. Then, the first batch of powder is put into a cement mortar mixer and mixed for 90 seconds. Then, water accounting for 10% of the mass of the first batch of powder is added and mixed for 120 seconds. After the mixture is evenly mixed, the mixture is put into a mold and pressed into a second batch of material cakes (the second batch of material cakes is 3cm thick and 8cm in diameter) by a hydraulic press. The second batch of material cakes is placed in an electric heating blast drying oven and dried for 30 minutes (drying temperature is 100℃). S9. Preparation of Low-Carbon Powder II: Powder II is placed in a covered corundum crucible, and then the crucible is placed in a muffle furnace for high-temperature calcination (calcination regime: from room temperature to 300℃ at a heating rate of 3℃ / min, then held for 35 min; then from 300℃ to 1300℃ at a heating rate of 10℃ / min, then held for 35 min). After calcination, it is rapidly cooled by air to obtain the high-temperature calcined product. This product is then crushed by a jaw crusher to a combined material particle size ≤2mm. The combined material particle size is then ground in a cement ball mill to a specific surface area of 550m². 2 / kg, yielding low-carbon powder II; Preparation of S10 and Powder 3: First, use a vibrating screen to remove impurities from fluorogypsum and lithium slag, then dry them in a 105℃ electric heating blast drying oven until constant weight. Then, put the dried fluorogypsum and lithium slag into a planetary ball mill at a mass ratio of 3:1 and mix them evenly to obtain Powder 3 for later use. S11. Pretreatment of Waste Aerated Concrete: First, the waste aerated concrete is screened using a vibrating screen to remove impurities such as bricks and organic matter. Then, large pieces of waste aerated concrete are sawn into blocks less than 25cm in length, less than 6cm in thickness, and less than 12cm in width using a woodworking saw. Next, the blocks are crushed into 1-3mm particles using a jaw crusher. The particles are then dried in a 105℃ electric heating forced-air drying oven until constant weight is achieved. A portion of the dried waste aerated concrete particles is then ground in a cement ball mill to achieve a specific surface area of 400 m². 2 / kg of waste aerated concrete powder is reserved for use; Preparation of S12 and Powder 4: Powder 1 from S2, oil shale slag powder from S1, ferromanganese slag powder from S4, fly ash particles from S6, powder 3 from S10, and silica fume are mixed evenly in a mass ratio of 17%:9%:27%:25%:10%:12% to obtain mixture E. A water-reducing agent is added to mixture E, and then it is ground in an ultrafine grinding mill to obtain a specific surface area of 1800 m². 2 / kg of powder material four, of which the water-reducing agent accounts for 5% of the total mass of mixture E; S13. Preparation of coconut shell fiber: ① First, rinse the coconut shells with high-pressure water, then place them in a cool place to dry. Next, use a woodworking saw to cut the coconut shells into 8cm long pieces. ② Immerse the cut pieces in a container containing deionized water and triacylglycerol hydrolase (the amount of triacylglycerol hydrolase is 0.6% of the mass of deionized water) for 5 hours, maintaining the solution temperature at 48℃. Then filter and remove the coconut shell pieces. ③ Place the pieces in a 0.7% sodium hydroxide solution and heat and pressurize them (temperature 100℃). 4. Steam the coconut shell fragments at ℃ and 13MPa for 4 hours. After steaming, rinse the fragments with clean water. 5. Place the rinsed coconut shell fragments in a 70℃ electric hot air drying oven to dry to constant weight. Then, put them into a spinning machine to break them down into coarse fibers. Rinse them with clean water. 6. Place the rinsed coarse fibers in a 70℃ electric hot air drying oven to dry to constant weight. Then, loosen them using a carding machine to obtain coconut shell fibers with a diameter of 12~24μm. Then, make the coconut shell fibers with a diameter of 12~24μm into two sizes with a length of 19mm and 5~25mm for later use. S14. Preparation of Ultra-High Performance Concrete (UHPC): A dry mixture of powder and coarse / fine aggregates (component 1) is placed in a cement mortar mixer and dry-mixed for 250 seconds. The powder includes powder 2 and powder 4, and the coarse / fine aggregates are coarse and fine sand. The mass percentages of coarse / fine sand, powder 2, and powder 4 are 45%:40%:15%. Water is divided into three equal parts by mass and mixed separately with defoamer, retarder, and high-performance expanding agent. After complete dissolution, two parts of the solution are poured onto the dry mixture (component 1) and stirred for 210 seconds until the dry mixture becomes similar to a dough. Then, the remaining 1 part of the solution is added, and the mixture is stirred for another 210 seconds to bring the slurry to a viscous state. The amounts of expanding agent, defoamer, retarder, and water are 2.9‰, 0.96‰, 0.58‰, and 20% of the total mass of the powder, respectively. The fiber is slowly added to the mixer in the stirring state over 390 seconds. After the fiber is added, the mixture is stirred for another 250 seconds to obtain ultra-high performance concrete. The fiber includes steel fiber and 19mm long coconut shell fiber from S13. The amount of coconut shell fiber and steel fiber added accounts for 0.4 vol.% and 2.3 vol.% of the total volume of ultra-high performance concrete, respectively. (UHPC fireproof board can be obtained by pouring ultra-high performance concrete into a mold and compacting it with a vibrating table. After standard curing for 1 day, the mold is removed and immediately placed in a steam curing chamber at 90℃ for 3 days.)
[0064] S15. Preparation of foamed concrete: The dry materials and 5-25mm long coconut shell fibers from S13 are placed in a cement mortar mixer and mixed evenly according to the specified ratio. The dry materials are powder II from S9, waste aerated concrete powder from S11, and powder IV from S12, with a mass percentage of powder II, waste aerated concrete powder, and powder IV of 35%:10%:55%. The amount of coconut shell fiber added is 0.3 vol.% of the total volume of the foamed concrete. Then, 55% of the water is added according to a water-to-material ratio of 72%. Mix 10‰ of warm water and foam stabilizer (total water volume) for 100 seconds, then add 0.70‰ of aluminum powder (total dry material mass) and mix for 50 seconds to obtain foamed concrete. (Ensure the pouring temperature of the foamed concrete is 50℃. After pouring into the mold, allow it to stand still and steam for 10 hours at 64℃, then perform standard curing for 2 days before demolding. Immediately after demolding, place it in a steam curing chamber at 90℃ for 3 days to obtain foamed concrete slabs.)
[0065] The mass percentage of coarse sand to fine sand in the coarse sand is 3:1. The mass percentage of fine sand (0.109~0.212mm ferrosilicon slag particles and quartz sand) is 2:1. The mass percentage of coarse sand (0.212~0.380mm ferrosilicon slag particles and quartz sand) is 3:1. Two types of steel fibers (0.2mm and 0.16mm in diameter) are used in a mass percentage ratio of 2:1. The foam stabilizer contains trinitrotoluene, distilled water, and sodium stearoyl lactylate in a ratio of 9%:80%:11%. In S2 and S8, the pressing pressure is 25 MPa. In S5, S6, and S10, the planetary ball mill dispersion time is 20 min. In S9, cooling includes first cooling to 1000℃ at a wind speed of 20℃ / min, and then cooling to room temperature.
[0066] The powder prepared by S10, a 3:1 mixture of fluorogypsum and lithium slag, meets the technical specifications specified in GB / T 21371-2019 "Industrial By-product Gypsum Used in Cement". The mixed industrial by-product gypsum contains 92% CaSO4·2H2O and 92% CaSO4, with a chloride ion content of 0.33%, a pH value of 4.1, and radioactive material limits that meet the requirements of GB 6566.
[0067] In Example 3, the properties of the relevant components are shown in the table below.
[0068] Table 13 Physicochemical properties of powder 1 in Example 3-S2 ; *Note: refers to the technical specifications of JC / T 621-2021, "Quicklime for Silicate Building Products".
[0069] Table 14 Chemical composition of low-carbon powder II in Example 3-S9 ; Table 15 Activity Index of Low Carbon Powder II in Example 3 – S9
[0070] ; Note: * indicates the test method in GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)".
[0071] Table 16 Radioactivity test results of dry material in Example 3-S12 ; *Note: These are the test requirements in GB 6566-2010, "Limits of Radionuclides in Building Materials".
[0072] Table 17 Performance Indicators of UHPC Boards in Example 3-S14 ; Note: * represents T / CECS 10107-2020, Technical Requirements for Ultra-High Performance Concrete (UHPC); ** represents GB / T 31387-2025, Ultra-High Performance Concrete; *** represents GB 8624-2012, Classification of Combustion Performance of Building Materials and Products.
[0073] Table 18 Performance Indicators of Foamed Concrete Boards in Examples 3-S15 ; Note: * indicates the test index requirements in "Foamed Concrete" JG / T 266-2011.
[0074] The composition and structure of the foamed concrete in S15 of Example 2 are analyzed as follows.
[0075] (1) Mineral composition of foamed concrete
[0076] First, XRD diffraction analysis was performed, and then the obtained data was analyzed using Jade software, comparing it with the XRD chart. Then, Origin software was used to plot the data, labeling the main diffraction peaks and analyzing the phase composition. Figure 5XRD patterns of the hardened foamed concrete paste after 28 days of standard curing are presented. The mineral composition of the hardened paste, as observed in the figures, consists of ettringite (AFt), portlandite (Ca(OH)2), tobeimorite, anhydrite (CaSO4), calcite, and quartz. When the composite cementitious material system used to prepare foamed concrete comes into contact with water, the active minerals C3S, C4AF, C3A, and C2S contained in the low-carbon powder of the system undergo hydration reactions, generating CSH gel and Ca(OH)2. Figure 5 The presence of a distinct "bun peak" at 25–35 °C indicates the formation of low-crystallinity amorphous substances and CSH gel within the hardened slurry. As the curing period extends, the CSH gel continues to deposit, causing the cementitious slurry to gradually transition from thickening to hardening, and the macroscopic strength of the specimen rapidly increases.
[0077] It should be emphasized that the ultrafine powders used in foamed concrete, such as oil slag powder, ferromanganese slag powder, fly ash, silica fume, and waste aerated concrete, also contain amorphous glass (CaO). m (SiO2) n (Al2O3) k In the alkaline environment of foamed concrete slurry, the vitreous body undergoes a pozzolanic reaction, during which the active components Al2O3 and SiO2 in the vitreous body are gradually consumed by Ca(OH)2. Figure 5 The presence of Ca(OH)2 in the hardened slurry indicates that the Ca(OH)2 in the slurry was not completely consumed. Figure 5 The quartz minerals present are residues of inert SiO2 from ultrafine powders in oil slag, ferromanganese slag, fly ash, silica fume, and waste aerated concrete. These, along with tobermorite and calcite in the waste aerated concrete, have a significant physical filling effect on the cementitious system, contributing to improved structural density. In the alkaline environment of the slurry, the glassy components in the ultrafine powder undergo Al-O and Si-O dissociation, resulting in [AlO4]. 5- [SiO4] 4+ The disruption of the tetrahedral network structure promotes the depolymerization of the glass phase and releases dissolved silicon and aluminum into the solution, ultimately leading to the formation of Al. 3+ Ca 2+ Na + The plasma recombines in the aqueous solution and undergoes a complex reaction to form a CSH gel, which then reacts with SO4 from the fluorogypsum and lithium slag in the solution. 2- The reaction produces AFt. Figure 5The presence of gypsum diffraction peaks at approximately 12°, 30°, and 35° indicates that during curing and hydration, gypsum is not completely consumed, and the remaining gypsum acts as a physical filler in the hardened foamed concrete. With increasing curing age, hydration products such as CSH gel and AFt crystallize, grow, and nucleate, eventually interacting and overlapping to form a new network structure, thus ensuring the strength of the foamed concrete.
[0078] (2) Pore structure of foamed concrete
[0079] Foamed concrete incorporates numerous air bubbles, most with pore sizes less than 1 mm. Scanning electron microscopy (SEM) analysis of the pore structure of foamed concrete primarily focuses on the uniformity of pore distribution, pore size, and the distribution of porous materials within the foamed concrete. Uneven pore size distribution significantly impacts the compressive strength of the material, while locally large pores become the weakest points. This is because stress concentrates at these large pores under pressure, initially causing microcracks that then spread to other areas with larger pore sizes. As these cracks propagate, the specimen eventually fails. Therefore, to improve the material's strength, it is essential to control the uniformity and size of the air bubbles. This requires the prepared foam to have small, uniform, and closed pore sizes.
[0080] like Figure 6 As shown, a cross-section of a foamed concrete specimen reveals that the foamed concrete product is a composite of numerous pores and pore walls of varying sizes. The pores are formed by foam in the slurry and become fixed within the concrete during the hardening process. The pore walls consist of hydration products, unreacted material particles, and voids within the pore walls. The presence of these voids alters both the density and strength of the product. It also improves the product's thermal insulation and frost resistance.
[0081] From a macroscopic perspective, foamed concrete consists of pores and pore walls. The pore walls of calcium silicate foamed concrete typically contain silica particles of varying sizes, residual nuclei from the reaction, and unhydrated portions of cementitious particles. Between these solid particles, numerous hydration products and micropores or gaps of different shapes and sizes accumulate, forming a framework of silica particles. Hydrated silicate colloids and crystals adhere to this framework, resulting in a heterogeneous solid-liquid-gas three-phase aggregate structure with various micropores and other defects. Within the pore wall structure, the various materials are not only in direct contact or mechanical interlocking with each other, but also bonded together with more rigid hydration products formed through chemical reactions under high pressure, high humidity, and high heat conditions. This is the primary reason why the pore walls can withstand external forces.
[0082] In this invention, powder two, as the main calcareous material used in foamed concrete, is the primary source of Ca(OH)2 in the foamed concrete slurry. The setting and hardening action of powder two causes the foamed concrete slurry to gradually thicken and eventually set and harden to form a green body. The Ca(OH)2 released from powder two reacts with SiO2 and Al2O3 in the ultrafine powder material to generate hydrated calcium silicate and hydrated calcium aluminum silicate. Powder two plays a crucial role in achieving strength in foamed concrete. Waste aerated concrete, as fine aggregate, is the main source of SiO2 in foamed concrete. During the hydration process of powder two, Ca(OH)2 reacts with SiO2 and Al2O3 in the fine sand to generate hydrated calcium silicate and hydrated calcium aluminum silicate, forming the "skeleton" of the foamed concrete and playing a vital role. Foamed concrete produced using waste aerated concrete has a low density, resulting in higher strength, lower drying shrinkage, better frost resistance, and less susceptibility to cracking.
[0083] (3) Microstructure of foamed concrete
[0084] Figure 7 The triangular structure in region 1 is a cross-sectional hydration product structure. Figure 11 The composition of hydration products after magnification of the triangular structure is shown. The product composition that can be clearly seen in the field of view is CSH gel, needle-shaped ettringite and plate-shaped Ca(OH)2. The ettringite grows in a concentrated manner on the surface of CSH gel. Figure 7 Cracks appeared in the inner wall structure of the pores in region 2; Figure 7 Region 3 shows the morphology of hydration products in the pore inner wall structure. Figure 10 The hydration products after magnification show that the hydration products in the field of view are CSH gel, fibrous ettringite and two rod-like, layered crystals, which are presumed to be Ca(OH)2. Figure 8 The hydration products in region 4 are shown after magnification. Figure 12 and Figure 13 This area contains hydration products on the inner surface of the pores. Within the field of view, the products are fibrous ettringite that grows from clusters to dots, and there is a small amount of CSH gel. Figure 9 Region 5 in the image shows the magnified morphology of the product. Figure 14 The hydration products within the field of view mainly appear as Ca(OH)2 crystals in a plate-like layered structure.
Claims
1. A method for preparing building materials based on multi-source solid waste, characterized in that, Includes the following steps: S1. Pretreatment of oil shale residue: After screening and removing impurities, oil shale residue is crushed and dried to obtain oil shale residue particles. Some particles are ball-milled to obtain oil shale residue powder. S2. Pretreatment of ammonia-alkali white mud and kitchen shell waste: Kitchen shell waste is washed, air-dried, crushed, baked and ball-milled to obtain shell powder. Ammonia-alkali white mud and shell powder are mixed and stirred, water is added, put into mold, pressed, dried, calcined, cooled and ball-milled to obtain powder one. S3. Waste photovoltaic panel pretreatment: After removing the attached materials, cleaning and drying, the waste photovoltaic panels are crushed to obtain waste photovoltaic panel particles of a specific size. S4. Pretreatment of ferromanganese slag: Ferromanganese slag is screened and dried to obtain ferromanganese slag particles of different sizes. Some particles are ball-milled to obtain ferromanganese slag powder. S5. Pretreatment of lead-zinc slag and vanadium-titanium ore slag: Lead-zinc slag and vanadium-titanium ore slag are screened, crushed and dried to obtain corresponding particles, which are then mixed with ferromanganese slag powder to obtain particle mixture B. S6. Pretreatment of fly ash and coal gangue: Fly ash is dried and ball-milled to obtain fly ash particles; coal gangue is screened, crushed, and dried to obtain coal gangue particles; the two are mixed to obtain granular mixture C. S7. Pre-treatment of wooden packaging for express delivery: The wooden packaging for express delivery is disassembled, sawn into pieces, carbonized, and then crushed to obtain carbon particles; S8. Preparation of Material Cake 2: Mix oil shale slag particles, powder 1, waste photovoltaic panel particles, granular mixture B, and granular mixture C to obtain mixture D. Add carbon particles to mixture D and ball mill to obtain combined powder 1. Dry mix combined powder 1, add water and mix, put into mold, press, and dry to obtain material cake 2. S9. Preparation of Powder II: Low-carbon powder II is obtained by calcining, cooling, crushing and ball milling the powder cake II at high temperature; S10. Preparation of Powder 3: Fluorogypsum and lithium slag that have been screened to remove impurities and dried are put into a planetary ball mill and mixed evenly to obtain powder 3; S11. Pretreatment of waste aerated concrete: Waste aerated concrete is screened to remove impurities, sawn into pieces, crushed and dried to obtain waste aerated concrete particles. Some of the particles are ball-milled to obtain waste aerated concrete powder. S12. Preparation of Powder 4: Mix Powder 1, oil shale slag powder, ferromanganese slag powder, fly ash particles, Powder 3 and silica fume evenly to obtain mixture E. Add water-reducing agent to mixture E, and then grind to obtain Powder 4. S13. Preparation of coconut shell fiber: Coconut shells are processed to obtain coconut shell fibers of a specific size; S14. Preparation of Ultra-High Performance Concrete: Dry-mixed powder and coarse / fine aggregate (component 1) is placed in a cement mortar mixer and mixed for 210-250 seconds. The powder includes powder 2 and powder 4, and the coarse / fine aggregate is coarse / fine sand. The mass percentages of coarse / fine sand, powder 2, and powder 4 are 45-58%:32-40%:10-15%. Water is divided into three equal parts by mass and mixed separately with defoamer, retarder, and high-performance expanding agent. After complete dissolution, two parts of the solution are poured onto the dry-mixed powder (component 1) and stirred for 180-210 seconds until the dry-mixed powder (component 1) becomes a dough-like consistency. Then, the remaining... One part of the solution is added, and the mixture is stirred for 180-210 seconds to bring the slurry to a viscous state. The amounts of expanding agent, defoamer, retarder, and water are 1.5-2.9‰, 0.77-0.96‰, 0.38-0.58‰, and 18-20% of the total mass of the powder, respectively. The fiber is slowly added to the mixer during the stirring process over 340-390 seconds. After the fiber is added, the mixture is stirred for another 210-250 seconds to obtain ultra-high performance concrete. The fiber includes steel fiber and 19mm long coconut shell fiber, with the coconut shell fiber and steel fiber accounting for 0.1-0.4 vol.% and 1.7-2.3 vol.% of the total volume of the ultra-high performance concrete, respectively. S15. Preparation of foamed concrete: Dry materials and 5-25mm long coconut shell fibers are placed in a cement mortar mixer and mixed evenly in proportion. The dry materials are powder II, waste aerated concrete powder, and powder IV, wherein the mass percentages of powder II, waste aerated concrete powder, and powder IV are 35-60%: 5-10%: 35-55%. The amount of coconut shell fiber added is 0.1-0.3 vol.% of the total volume of foamed concrete. Then, warm water at 48-55℃ and a foam stabilizer of 6-10‰ of the total water volume are added at a water-to-material ratio of 52-72%. The mixture is stirred for 80-100 seconds. Then, aluminum powder of 0.55-0.70‰ of the total mass of the dry materials is added and stirred for 30-50 seconds to obtain foamed concrete.
2. The method for preparing building materials based on multi-source solid waste according to claim 1, characterized in that, The particle size of the oil shale residue in S1 is 2-5 mm, and the specific surface area of the oil shale residue powder is 200-300 m². 2 / kg; the specific surface area of the shell powder in S2 is 200~300 m² 2 / kg, ammonia-alkali white mud and shell powder are mixed at a mass ratio of 2~4:1~3, and the specific surface area of powder one is 400~500m². 2 / kg; the particle size of waste photovoltaic panel particles in S3 is ≤2mm; in S4, ferrosilicon slag is screened and dried to obtain ferrosilicon slag particles with particle sizes ≤0.109mm, 0.109~0.212mm, 0.212~0.380mm, and ≥0.380mm. The dried ferrosilicon slag particles with particle sizes ≤0.109mm and ≥0.380mm are then ground in a cement ball mill to obtain a specific surface area of 200~300m². 2 / kg of ferrosilicon manganese slag powder is reserved; In S5, the particle size of lead-zinc slag particles and vanadium-titanium ore slag particles is ≤2mm. The lead-zinc slag particles, vanadium-titanium ore slag particles, and ferrosilicon manganese slag powder are mixed in a planetary ball mill at a mass ratio of 1~3:1:2~4 to obtain granular mixture B with a particle size ≤2mm; In S6, the particle size of fly ash particles is ≤2mm, and the particle size of coal gangue particles is ≤2mm. The fly ash particles and coal gangue particles are mixed in a planetary ball mill at a mass ratio of 2~4:1~3 to obtain granular mixture C with a particle size ≤2mm; In S7, the particle size of carbon particles is ≤2mm; In S8, oil shale slag particles, powder one, waste photovoltaic panel particles, granular mixture B, and granular mixture C are mixed at a mass ratio of 10~15%:60~77%:5~10%:5~10%:3~5%, and the specific surface area of the combined powder one is 300~400m². 2 / kg, carbon particles account for 5~8% of the total mass of mixture D; the specific surface area of powder II in S9 is 450~550m². 2 / kg; in S10, fluorogypsum and lithium slag are mixed at a mass ratio of 1~3:1; in S11, the particle size of waste aerated concrete particles is 1~3mm, and the specific surface area of waste aerated concrete powder is 300~400 m². 2 / kg; S12 contains powder one, oil shale slag powder, ferromanganese slag powder, fly ash granules, powder three, and silica fume mixed in a mass ratio of 13~18%:6~10%:24~28%:21~26%:7~11%:12~29%, and powder four has a specific surface area of 1600~1800 m². 2 / kg, the water-reducing agent accounts for 3~5% of the total mass of mixture E; the diameter of coconut shell fiber in S13 is 12~24μm, and the length is 19mm or 5~25mm.
3. The method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, The silica fume in S12 has a particle size of 0.1~1µm. Its SiO2 content, apparent density, specific surface area, and pozzolanic activity index are 91.38%, 2.18 g / cm³, and 1 μm, respectively. 3 19400m 2 / kg, 110%; the water-reducing agent in S12 is a high-performance polycarboxylate powder water-reducing agent with a water reduction rate of >30%.
4. A method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, The main chemical elements of coconut shell fiber in S13 are: C 45~55%, H 3~8%, O 40~52%, N 0.2~1.5%, S 0.01~0.2%. This coconut shell fiber contains 40~50% total cellulose, 15~20% lignin and 30~40% α-cellulose.
5. A method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, S14 contains coarse and fine sand, including fine sand with a particle size of 0.109~0.212mm and coarse sand with a particle size of 0.212~0.380mm. The mass percentage of coarse sand to fine sand is 1~3:
1. The mass percentage of fine sand containing ferromanganese slag particles with a particle size of 0.109~0.212mm and fine quartz sand is 1~2:
1. The mass percentage of coarse sand containing ferromanganese slag particles with a particle size of 0.212~0.380mm and coarse quartz sand is 1~3:
1.
6. A method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, In S14, the defoamer is at least one of tributyl phosphate or organosilicon defoamer, the retarder is boric acid, and the main chemical composition and content of the high-performance expander are SiO2 5~10%, Al2O3 25~30%, Fe2O3 1~7%, CaO 30~40%, MgO 1~3%, SO3 18~23%, and the loss on ignition of the high-performance expander is 0.1~1%.
7. A method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, The fibers used in UHPC in S14 are steel fibers and coconut shell fibers. The steel fibers used are of two types: 0.2 mm in diameter and 13 mm in length, and 0.16 mm in diameter and 6 mm in length. The two types of steel fibers are used in a mass ratio of 1 to 2:
1. The cement mortar mixer is used at a low speed during the preparation of UHPC slurry.
8. A method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, The foam stabilizer in S15 is formulated from trinitrotoluene, distilled water and sodium stearoyl lactylate, with the corresponding ratio of trinitrotoluene, distilled water and sodium stearoyl lactylate being 6~9%: 80~92%: 2~11%; the active Al content of aluminum powder in S15 is ≥93%.
9. A method for preparing building materials based on multi-source solid waste according to claim 2, characterized in that, Crushing is performed using jaw crushers in processes S1, S2, S5, S6, S7, S9, and S11, with a feed size ≤250mm and a discharge size ≤10mm. Cement ball mills are used in processes S1, S2, S4, S8, S9, and S11, with a speed of 48 r / min. Hydraulic presses are used in processes S2 and S8, with a pressing pressure of 15~25 MPa. Cement mortar mixers are used in processes S2, S8, S14, and S15, with low-speed mixing at the following speeds: rotation speed 140±5 r / min, revolution speed 62±5 r / min, or rotation speed 285±10 r / min, revolution speed 125±10 r / min. The mixing speed is 200 r / min; in S5, S6 and S10, a planetary ball mill is used for mixing, with a mixing time of 15~20 min and a rotation speed of 200 r / min; in S9, cooling includes: first cooling to 1000℃ with air at a speed of 18~20℃ / min, and then cooling to room temperature; in S3, the waste photovoltaic panels are first crushed into fragments by a hammer crusher, and then the fragments are crushed into waste photovoltaic panel particles with a particle size ≤2mm by a jaw crusher, wherein the feed particle size of the hammer crusher is ≤450mm and the discharge particle size is ≤25mm, and the feed particle size of the jaw crusher is ≤250mm and the discharge particle size is ≤10mm; in S11, the maximum feed particle size of the ultrafine grinding mill is ≤20mm, and the finished particle size is 325~2500 mesh.
10. A high-strength thermal insulation board, characterized in that, The material includes a polyurethane board in the middle layer, on both sides of which are successively provided foamed concrete board layers and ultra-high performance concrete board layers. A steel grid is provided between the foamed concrete board layers and the ultra-high performance concrete board layers. The foamed concrete board layers are formed by casting foamed concrete prepared as described in claim 1, and the ultra-high performance concrete board layers are formed by casting ultra-high performance concrete prepared as described in claim 1.
Citation Information
Patent Citations
Method for preparing high-performance concrete from gneiss waste rocks and waste photovoltaic panels
CN110981401A
Method for preparing aerated concrete slab from lithium-containing slag-steel slag-coal-based solid waste
CN118619652A